Angelita...ako ang iyong ina (Manila Aquarious Records & Tapes)
Angelita ako ang iyong ina is a sequel of the super hit movie Mga Mata ni Angelita that made Julie Vega a child superstar, a story of a girl searching for the love and care of her real mother and also a story of sacrifice and love that cannot be equaled. it also stars the incomparable Susan Roces as her real mother.
DVD
Susan Rosces, Julie Vega.
Keywords: Feature Films